This problem can be solved directly by neglecting the
initial velocity given. All we have to do is to plug in t = 4 in the given
equation. That is:
h = -16^2 + 123 * 4
h = 236 ft
Answer:
I hope this helps!Let me know if it helps
Step by Step :
1. 9(2j + 7 + 5j)
2. (9)(2j) + (9)(7) + (9)(5j)
3. 18j + 63 + 45j
Answer: 63j + 63
The value of the highlighted variables ave been determined a =6, b= 2 ,c= 6 , d = 2 , e = 6 , f = 6, g =1
<h3>What is an Expression ?</h3>
An expression are mathematical statement consisting of variables , constants and mathematical operators .
The given expression is
![\rm \dfrac{2}{x^2-36} - \dfrac{1}{x^2 +6x} = \dfrac{2}{(x+6)(x-6)}-\dfrac{1}{x(x+a)}\\\\= \dfrac{bx}{x(x+6)(x-6)}-\dfrac{x-c}{(x+6)(x+6)x}\\\\= \dfrac{dx-x+e}{x(x+6)(x-6)}\\\\= \dfrac{x+f}{x(x+6)(x-6)}\\\\= \dfrac{g}{x(x-6)}](https://tex.z-dn.net/?f=%5Crm%20%5Cdfrac%7B2%7D%7Bx%5E2-36%7D%20-%20%5Cdfrac%7B1%7D%7Bx%5E2%20%2B6x%7D%20%3D%20%5Cdfrac%7B2%7D%7B%28x%2B6%29%28x-6%29%7D-%5Cdfrac%7B1%7D%7Bx%28x%2Ba%29%7D%5C%5C%5C%5C%3D%20%5Cdfrac%7Bbx%7D%7Bx%28x%2B6%29%28x-6%29%7D-%5Cdfrac%7Bx-c%7D%7B%28x%2B6%29%28x%2B6%29x%7D%5C%5C%5C%5C%3D%20%5Cdfrac%7Bdx-x%2Be%7D%7Bx%28x%2B6%29%28x-6%29%7D%5C%5C%5C%5C%3D%20%5Cdfrac%7Bx%2Bf%7D%7Bx%28x%2B6%29%28x-6%29%7D%5C%5C%5C%5C%3D%20%5Cdfrac%7Bg%7D%7Bx%28x-6%29%7D)
a = 6
b= 2
c= 6
d = 2
e = 6
f = 6
g =1
Therefore the value of the highlighted variables ave been determined.
To know more about Expression
brainly.com/question/14083225
#SPJ1
3 blocks east and 2 blocks north should be the correct answer :)